General bounds for electrode mislocation on the EEG inverse problem - Beltrachini, Leandro (2011)
We analyze the effect of electrode mislocation on the electroencephalography (EEG) inverse problem using the Cramér–Rao bound (CRB) for single dipolar source parameters. We adopt a realistic head shape model, and solve the forward problem using the Boundary Element Method; the use of the CRB allows us to obtain general results which do not depend on the algorithm used for solving the inverse problem. We consider two possible causes for the electrode mislocation, errors in the measurement of the electrode positions and an imperfect registration between the electrodes and the scalp surfaces. For 120 electrodes placed in the scalp according to the 10–20 standard, and errors on the electrode location with a standard deviation of 5 mm, the lower bound on the standard deviation in the source depth estimation is approximately 1 mm in the worst case. Therefore, we conclude that errors in the electrode location may be tolerated since their effect on the EEG inverse problem are negligible from a practical point of view.